The global climate change footprint in a Mexican desert ecosystem: The increasing frequency of extreme climatic events - Montiel-González, Cristina; García-Oliva, Felipe; Bautista, Francisco; Sánchez-Meneses, Oscar (Tecnología y ciencias del agua, 2021)
While the accuracy of scenarios of Global Climate Change has been improved, the lack of climatic data from several regions of the world means that some predictions remain misleading. The local climate studies are critical for the calibration of global climate scenarios. Our objective was to evaluate the climate trends within the Cuatro Ciénegas Basin (CCB). Specifically, we aimed to: 1) identify potential trends in the behavior of temperature and precipitation; 2) assess the nature and direction of changes in the frequency of extreme climate events (ECE); and 3) detect changes in inter-annual precipitation variability. To achieve these aims, we analyzed a 70-year database of climatic variables from the CCB weather station. Data were subjected to trend analyses using two different software packages; ECE frequency was evaluated by Chi-square analysis and precipitation data was analyzed by the standardized pluviometric drought index Minimum temperature (Tmin) increased in almost 2 °C every month, while mean temperature (Tmean) increased 2 °C but only in the summer months. Lower Tmin frequency increased two times or higher in the winter months, while the frequency of upper event extremes increased at least three times during the summer months, as did the extreme events of maximum temperature (Tmax). Winters have therefore become colder while summers have become warmer, increasing the frequency of heat waves over the last 36 years. However, monthly precipitation patterns presented high variability that obscured any trend in the ECE of precipitation events. Over the last 36 years, frequencies of events of both intense precipitations associated with tropical cyclones and intense drought associated with the ENSO were higher than before.